Answer:
The solution is (-5,4).
Step-by-step explanation:
We are given the equation, |x+1|=|-x-9|
Now, |x+1| = [tex]\left\{\begin{matrix}x+1 & ,x>0\\ -(x+1)& ,x<0\end{matrix}\right.[/tex]
Also, |-x-9| = [tex]\left\{\begin{matrix}-x-9 & ,x>0\\ -(-x-9)& ,x<0\end{matrix}\right.[/tex]
So, equating these two functions gives the value of x = -5. After substituting this value in any of the function term say y = x+1, we get y = 4.
Moreover, from the graph below we see that, after equating these functions, the solution is given by the points at which they intersect.
Hence, the solution is (x,y) = (-5,4).